Bimetallic salen aluminum complexes: cooperation between reactive centers in the ring-opening polymerization of lactides and epoxides. Issue 40 (11th August 2016) - Isnard, Florence; Lamberti, Marina; Lettieri, Luana; D'auria, Ilaria; Press, Konstantin; Troiano, Rubina; Mazzeo, Mina
Abstract : In dinuclear aluminum complexes, opportunely designed to have proximal coordinative pockets, the communication between the two reactive centers allows enhanced catalytic performances. Abstract : Three dinuclear aluminum alkyl complexes of the general formula LAl2 Me4, where L are salen ligands with an alkyl backbone of different lengths between the nitrogen atoms (1, 3-propylene (1 ), 1, 5-pentylene (2 ) and 1, 12-dodecaylene (3 )), have been prepared through alkane elimination reactions between each ligand and two equivalents of AlMe3 . The related hemi-salen aluminum complex4 was prepared by an analogous reaction between a phenoxy–imine ligand and a single equivalent of AlMe3 . The activities of these aluminum complexes in the ring-opening polymerization (ROP) of rac -lactide and of several epoxides have been investigated and compared. The dinuclear complex1, bearing the salen ligand with the shortest alkyl bridge, was the most active in the ROP of LA producing isotactic enriched PLA. Otherwise, the other complexes (2 and3 ), in which the metal centers are remote, produced atactic PLA with inferior activity. Analogous differences in terms of activity emerged in the ROP of epoxides. The comparison of the catalytic behavior of the dinuclear complexes as well as their mononuclear counterparts suggests the cooperation between the two aluminum metal centers of the dinuclear species in which these are close enough.